2022
DOI: 10.1111/codi.16224
|View full text |Cite
|
Sign up to set email alerts
|

Mesh, flap or combined repair of perineal hernia after abdominoperineal resection – A systematic review and meta‐analysis

Abstract: Perineal hernia after abdominoperineal resection (APR) remains a vexing problem for both patients and clinicians. In the current literature the incidence of symptomatic perineal hernia ranges from 7% to 30% [1-3]. A perineal hernia may cause discomfort, pain, wound healing problems, urogenital dysfunction and small bowel obstruction [4][5][6]. Depending on the severity of symptoms, preference and experience of the surgeon, an elective repair is sometimes considered. In contrast to abdominal wall hernias, liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…More examination is still necessary to illuminate these possible impacts. This was similarly emphasized in former research that utilized a connected meta‐analysis practice and originated comparable values of the impact 40–42 . Though the meta‐analysis was unable to determine if differences in these variables are connected to the research results, properly‐led RCTs must take these factors into account in addition to the variety of diverse ages, gender, and ethnicities of people.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More examination is still necessary to illuminate these possible impacts. This was similarly emphasized in former research that utilized a connected meta‐analysis practice and originated comparable values of the impact 40–42 . Though the meta‐analysis was unable to determine if differences in these variables are connected to the research results, properly‐led RCTs must take these factors into account in addition to the variety of diverse ages, gender, and ethnicities of people.…”
Section: Discussionmentioning
confidence: 96%
“…This was similarly emphasized in former research that utilized a connected meta-analysis practice and originated comparable values of the impact. [40][41][42] Though the metaanalysis was unable to determine if differences in these variables are connected to the research results, properlyled RCTs must take these factors into account in addition to the variety of diverse ages, gender, and ethnicities of people. In conclusion, VRAM flap had significantly lower PWCs, and major PWCs compared to PC in AS and PE of anal and rectal cancers persons.…”
Section: Discussionmentioning
confidence: 99%
“…One less studied approach involves the combination of tissue flaps with mesh closure which may lead to less perineal hernia recurrence rates as the tissue flap fills the soft tissue defect and the mesh provides strength to the pelvic floor. Studies have shown low recurrence rates in patients with this type of repair [ 7 , 13 ], but data is lacking. Regardless of surgery type, poor wound healing in pCD patients may increase the likelihood of developing postoperative complications and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Following SPH repairs, the mesh must sustain direct pressure in standing and/or sitting positions and therefore, the mesh's strength becomes an important factor of surgical outcome. The mesh's weakness and breakability are probably the reasons why recurrence rates continue to be very high after repairs with biologic meshes [11]; therefore, durable meshes and sufficient fixations are preferable. Having considered all of the above-mentioned characteristics and difficulties of SPH repair, we used a mesh with a memory-recoil ring and placed it transperineally.…”
Section: Discussionmentioning
confidence: 99%